Measurement of applied force and deflection in the javelin throw - Maeda, M.; Shamoto, E.; Moriwaki, T.; Nomura, H. (Journal of Applied Biomechanics, 1999)
The present paper presents a new sensor to measure 6 components of force and 2 components of deflection applied to the javelin during the throw. Since the javelin is deflected and vibraled during throwing, measurement of force and deflection applied to the javelin will provide important information for throwers in how to better throw the javelin and to design javelins with better dynamic characteristics. The sensor is designed not to significantly change the static and dynamic characteristics of the javelin. The force sensor performs well in terms of linearity and crosstalk, and the javelin equipped with this sensor has similar characteristics to ordinary javelins. The present paper also presents an example of measurement in the javelin throw.